IMPLEMENTASI GAYA KEPEMIMPINAN YANG DITERAPKAN OLEH KARAKTER UTAMA “TSUBASA OZORA” PADA FILM CAPTAIN TSUBASA - Abda Yusri Arrizqi, Abdan Arrizqi (DIGICOM : Jurnal Komunikasi dan Media, 2024)
Leadership is a person's ability to influence other people or subordinates in a company or organization with the aim that the goals of the company or organization are achieved. This study aims to determine the implementation of charismatic and transformational leadership styles in the character Tsubasa Ozora in the film Captain Tsubasa using a qualitative approach. This research highlights the importance of charisma-based and transformational leadership charisma and transformational leadership performed by the main character in creating a successful and highly competitive team, especially in the context of sports. Through observation and observation of various movie scenes, this research explores the character's influence on the development of the soccer team through his leadership style. The results show that Tsubasa's charisma-oriented and transformational leadership significantly motivates team members to improve performance, collaborate effectively and achieve common goals. This study highlights the importance of the interaction between the leader's personal characteristics and transformational strategies in the context of sports teams